Peluang Usaha Jasa Desain Grafis Freelance untuk UMKM dan Startup - Muhammad Aris Fachrizal; Karsim Karsim; Yuyun Yuneroh; Sri Murningsih (Universitas Veteran Bangun Nusantara, 2025)
The development of the digital economy in Indonesia has opened up great opportunities for the growth of Micro, Small and Medium Enterprises (MSMEs) and startup companies. In an increasingly competitive market, visual identity and branding are crucial factors in attracting consumer attention and building brand loyalty. This study aims to analyze the business opportunities of freelance graphic design services as a solution to the branding needs of MSMEs and startups in Indonesia. The research method used is a literature review by analyzing various previous studies, secondary data, and case studies from freelance graphic design industry players. The results show that there is a very large market opportunity for freelance graphic design services because: the majority of MSMEs and startups need professional visual identity but have limited budgets to hire permanent designers, graphic design has been proven to increase product competitiveness through packaging, logos, and attractive promotional media, digital platforms make it easier for freelance designers to reach clients widely with low operational costs, and freelance work flexibility offers benefits for designers in determining rates and portfolios. The conclusion of this study confirms that freelance graphic design services have promising prospects as a sustainable business model, provided that designers are able to build a strong portfolio, understand the principles of rational pricing, and utilize digital technology optimally for marketing.